2017
DOI: 10.1111/ced.13283
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic inhibition of cell proliferation by combined targeting with kinase inhibitors and dietary xanthone is a promising strategy for melanoma treatment

Abstract: α-Mangostin is a dietary xanthone that displays various biological activities, and numerous reports have shown its efficacy in cancer prevention and inhibition. As most agents have been shown to be ineffective as single-agent therapy for malignant melanoma (MM), the principle of targeted chemotherapy for MM is to use effective inhibitors and combination methods. In this study, we tested the cytotoxicity of several kinase inhibitors, including the glycogen synthase kinase (GSK)-3 inhibitor CHIR99021, and rapamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…18) In recent years, xanthone derivatives have been received considerable attention in the field of medicinal chemistry because of their diversely biological functions, 20,21) such as anti-oxidant, 22) anti-hypertensive, 23) anti-convulsant, 24) anti-cholinesterase, 25) anti-malarial, 26) antimicrobial, 27) anti-inflammatory, 28) and anti-cancer activities. 29) Besides, they also served as the effective inhibitors of several enzymes like α-glycosidase, 30,31) topoisomerase, 32) proteinkinase, 33) aromatase. 34) Driven by both the biologically applied powers and the favorable pharmacological properties, indeed, xanthone skeleton has been defined as one of the privileged structural motifs for next stage of certain new drug screening and discovery.…”
Section: Introductionmentioning
confidence: 99%
“…18) In recent years, xanthone derivatives have been received considerable attention in the field of medicinal chemistry because of their diversely biological functions, 20,21) such as anti-oxidant, 22) anti-hypertensive, 23) anti-convulsant, 24) anti-cholinesterase, 25) anti-malarial, 26) antimicrobial, 27) anti-inflammatory, 28) and anti-cancer activities. 29) Besides, they also served as the effective inhibitors of several enzymes like α-glycosidase, 30,31) topoisomerase, 32) proteinkinase, 33) aromatase. 34) Driven by both the biologically applied powers and the favorable pharmacological properties, indeed, xanthone skeleton has been defined as one of the privileged structural motifs for next stage of certain new drug screening and discovery.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, in order to enhance the efficacy of α-mangostin and apigenin as chemotherapeutic agents for ovarian cancer, other application approaches could be applied, such as with fatty acid-conjugated compounds (41), or the synergistic inhibition induced by co-administration with other promising compounds (42). Moreover, the toxicity of these compounds in an in vivo model system, such as the rat, should be determined (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study by Wang and colleagues (2017) showed that 2 was active in vivo as it inhibited tumor incidence and hyperplasia induced by carcinogen 9,10dimethylbenz[a]anthracene (DMBA) and skin tumor promoter 12-O-tetra-decanoylphorbol-13-acetate (TPA) in ICR mice following daily intraperitoneal administration of 5 mg/kg or 20 mg/kg of the xanthone (Wang et al, 2017). The inhibition of cancer cell proliferation was hypothesized to be linked to the suppression of the PI3K/Akt signaling pathway by decreasing the phosphorylation of PI3K, Akt and TOR proteins (Wang et al, 2017;Xia and Sun 2018). The use of 5 μM of 2 as an adjunct to kinase inhibitors of the PI3K pathway such as rapamycin was also shown to be effective in inhibiting the proliferation of SK-MEL-28 cells (Xia and Sun 2018).…”
Section: Cytotoxic Mechanisms Of Xanthonesmentioning
confidence: 99%
“…The inhibition of cancer cell proliferation was hypothesized to be linked to the suppression of the PI3K/Akt signaling pathway by decreasing the phosphorylation of PI3K, Akt and TOR proteins (Wang et al, 2017;Xia and Sun 2018). The use of 5 μM of 2 as an adjunct to kinase inhibitors of the PI3K pathway such as rapamycin was also shown to be effective in inhibiting the proliferation of SK-MEL-28 cells (Xia and Sun 2018). Interestingly, despite antioxidative and ROS scavenging activity of 2 (Pedraza-Chaverri et al, 2009;Pérez-Rojas et al, 2009), the induction of ROS generation in melanoma cells may be a cytotoxic mechanism exhibited by the synergistic combination of 2 and kinase inhibitors (Xia and Sun 2018).…”
Section: Cytotoxic Mechanisms Of Xanthonesmentioning
confidence: 99%